Student Resilience in Responding to Climate Change in Coastal Areas of Demak Regency: Implications for SDGs - Eka Vasia Anggis; Elina Lestaryanti (Postgraduate, University of Mataram, 2026)
This study aims to describe the level of student resilience in facing climate change. The research subjects were senior high school students in Sayung and Bonang Subdistricts, Demak Regency. The study employed a mixed-methods approach with a sequential explanatory strategy, in which quantitative analysis is followed by qualitative exploration. Quantitative data were obtained through the analysis of student resilience questionnaires. Meanwhile qualitative data were gathered through in-depth interviews with teachers and students from the schools that served as research sites. The results of the study show that most students’ resilience also falls into the moderate category 49%, low 28%, and high 23%. Qualitative findings revealed that the school environment and family support were the main factors influencing this moderate level of resilience. In conclusion, resilience serves as an important factor that mediates students’ responses to environmental stress. This study recommends strengthening school support, improving adaptive facilities to climate change, and integrating disaster education into the coastal school curriculum to enhance student resilience.